HARNESSING ARTIFICIAL INTELLIGENCE TO COMBAT INFECTIOUS DISEASES: CHALLENGES AND OPPORTUNITIES (Journal of Medical & Health Sciences Review, 2025)
Infectious diseases remain a significant global health challenge, contributing to high morbidity and mortality rates, particularly in low- and middle-income countries. The COVID-19 pandemic underscored the urgent need for innovative solutions to prevent, detect, and manage infectious diseases effectively. Artificial intelligence (AI) has emerged as a transformative tool in healthcare, offering opportunities to enhance disease surveillance, diagnosis, treatment, and public health response. This research paper explores the potential of AI in combating infectious diseases, emphasizing its challenges and opportunities. A mixed-methods approach, incorporating literature review, case studies, and expert interviews, is used to identify key applications, limitations, and strategies for leveraging AI in global health. Recommendations for ethical implementation, data integration, and capacity building are provided to maximize the impact of AI in addressing infectious diseases.